Banking Behaviour and Political Business Cycle in Africa: The Role of Independent Regulatory Policies of the Central Bank - Daniel Ofori-Sasu; Elikplimi Komla Agbloyor; Dennis Nsafoah; Simplice Asongu (African Governance and Development Institute (AGDI), 2024)
This study examines the effect of regulatory independence of the central bank in shaping the impact of electoral cycles on bank lending behaviour in Africa. It employs the dynamic system Generalized Method of Moments (SGMM) Two-Step estimator for a panel dataset of 54 African countries over the period, 2004-2022. The study found that banks lend substantially higher during election years, and reduce lending patterns thereafter. The study shows that countries that enforce monetary policy autonomy of the central bank induce a negative impact on bank lending behaviour while those that apply strong macro-prudential independent action and central bank independence reduce lending in the long term. The study provides evidence to support that regulatory independence of the central bank dampens the positive effect of elections on bank lending around election years while they amplify the reductive effects on bank lending after election periods. There is a wake-up call for countries with weak independent central bank regulatory policy to strengthen their independent regulatory policy frameworks and political institutions. This will enable them better strategize to yield a desirable outcome of bank lending to the real economy during election years.
Keywords: D7; D72; G2; G3; E3; E5; E61; G21; L10; L51; M21; P16; P26; 330; Political Economy; Political Credit Cycles; Electoral Cycle; Central Bank Regulatory Independence; Bank lending Behaviour